Intellectual Capital and Firm Performance of Banking Industry in Nepal - Shrestha, Udaya Kumar; Wagle, Sudip (Journal of Business and Management, 2025)
Background: Intellectual capital as the sum of knowledge, information, intellectual property and experience that can provide competitive advantages and high value. Intellectual capital is the most important factor to enhance firm performance. Objectives: This study investigates the impact of intellectual capital on firm performance of banking industry in Nepal. Methods: This study employed descriptive and casual research design. A google form survey was given to bank executives in order to achieve the objectives of the study. Out of 234 possible respondents 141 respondents completed the questionnaire as adequate form, which were taken as sample through convenience sampling method. The firm performance was the dependent variable, and intellectual capital (human, structural, social, and customer capital) were the independent variable. Both descriptive and inferential analysis were used to examine the data. Regression analysis was formulated in a linear model to analyze the relationship between the variables. Results: The finding shows that the firm’s performance explained by human capital (β = 0.176, p = 0.090), structural capital (β = 0.003, p = 0.983), social capital (β = 0.307, p = 0.023) and customer capital (β = 0.270, p = 0.001). The relationship between intellectual capital (human, structural, and customer capital) and firm performance were a statistically significant positive association. In regression coefficient, social capital and customer capital were found to be significant predictors of firm performance, but human and structural capital were not statistically significant predictors. Conclusion: Social capital and customer capital were found to be significant predictors of firm performance, but human and structural capital were not statistically significant predictors. This study will appear as a successful piece of research work that explored both the intellectual capital conceptualization and orientation in the Nepalese banking industry. Furthermore, this study contributes to a better understanding of intellectual capital in Nepalese organization. JEL Classification: L25, M12, O34